Analisis Pengaruh Variasi Laju Aliran Air pada Sistem Pendinginan Modul Fotovoltaik dengan Simulasi CFD (Computational Fluid Dynamics) - Tomayahu, Syafril Agustion; Rozaq, M. Sya'banur; Romadhon, Rahmat; Pradipta, Justin; Haq , Irsyad N.; Leksono, Edi (Jurnal Otomasi Kontrol dan Instrumentasi, 2024)
Developing renewable energy is one of the main strategies to reduce greenhouse gas emissions and achieve global goals to limit global warming above pre-industrial temperatures. This study analyzes the effect of varying the cooling water flow rate on MS100-36 type polycrystalline photovoltaic modules through ANSYS Fluent 2024 R1 Student simulation. This simulation was conducted from 08:00 to 17:00, focusing on the influence of inlet water temperature on the temperature distribution of photovoltaic modules. The simulation results indicate thermal steady-state conditions at an irradiation of 463 W/m² with a natural coefficient of 5 W/m².There is a temperature distribution process occurring in the photovoltaic module under fluent conditions, where the effect of the inlet water temperature on the surface of the PV module is examined for a water temperature range of 20°C to 30°C in 5°C intervals, with water flow rates of 0.05, 0.1, and 0.2 kg/s. The contour images indicate that an increase in water flow rate can enhance the cooling effect of the photovoltaic module. Higher inlet water temperatures transfer less heat, producing higher temperatures for the photovoltaic modules. A water flow rate of 0.2 kg/s and an inlet water temperature of 20°C produce a lower and more uniform temperature distribution on the photovoltaic modules. Thus, increasing the water flow rate and decreasing the inlet water temperature have proven effective in enhancing the cooling performance of photovoltaic modules.